Development of IPAS Project Modules with the 4STMD Method to Facilitate Project-based Learning in Vocational School - Siti Darmilah; Sjaeful Anwar; Ida Kaniawati (Jurnal Penelitian Pendidikan IPA, 2025)
Teaching materials are one of the important components in learning. Especially project-based learning, students really need teaching materials that can help direct their learning. This study aims to develop teaching materials that can facilitate project-based learning in the subject of science projects in vocational high schools. The research method used is research and development, namely developing teaching materials in the form of modules with the 4STMD development method which stands for Four Steps Teaching Material Development. The 4STMD method has four stages of development, namely the selection, structuring, characterization and didactic reduction stages. The ability of teaching materials to facilitate learning is carried out by reading and understanding tests on grade 10 students at one of the vocational high schools in Sumedang Regency, West Java. Based on the results of the readability test by students, 97.9% stated that the module was easy to read, while the results of the understanding test showed that 84.5% stated that the module was easy to understand. The results of the readability and understanding tests showed that most of the text in the module was easy to understand by users, namely students. The results of the study can be concluded that teaching materials with the 4STMD method can facilitate project-based learning in the science project in vocational schools.